Pengaruh Metode Pancing Kata Kunci terhadap Kemampuan Menulis Puisi Berbantuan Media Karikatur pada Kelas X - Maghfirotul Mar’ah; Wika Soviana Devi (Arus Jurnal Pendidikan, 2022)
The low ability of students’ poetry writing, the learning activities must use one of the fun and interesting learning techniques for students using caricature image media. The use of appropriate media will make it easier for students to understand the poetry material explained by the teacher at school. This study aims to find out how to improve poetry writing skills and to determine the effect of keyword search techniques assisted by caricature media on the poetry writing skills of tenth grade students of MA Islamiyah Ciputat. This study uses a quantitative method with an experimental approach. The population selected by the researchers were students of class X for the academic year 2021/2022 with a total of 50 students. The sample was conducted by means of simple random sampling. The results showed that the experimental group had a significant difference in scores compared to the control group. The highest score was 40% with a range of 65-79 in the experimental class, while in the control class 30% in the range of 23-32. In learning in the experimental class, poetry writing skills using image media were more effective than not using image media for class X students in MA Islamiyah Ciputat.